Peran Pemerintah dalam Penegakan Hukum Digital di Indonesia: Antara Proteksi Warga, Ketertiban Siber, dan Risiko Otoritarianisme Digital - Gilang Rizki Aji Putra (UIN Jakarta, 2021)
Digital law enforcement requires governments to be not only regulatory but also responsive to technological change. This article explores the multidimensional role of the Indonesian government, including regulation, execution, supervision, and facilitation. Using normative legal research with statutory and conceptual approaches, the study finds that government roles remain fragmented and predominantly repressive rather than restorative. Despite progress in legislation, a persistent paradox exists between maintaining order and protecting digital rights. Cases of platform blocking illustrate tensions between sovereignty and freedom. The government must shift toward a more accountable, facilitative role. Keywords: Digital Law Enforcement, Government Role, Content Blocking, Digital Sovereignty, Accountability